Effect of seven or three weeks altitude training during a five month training period on hemoglobin mass and performance in national team cross country skiers - Wehrlin, J. P.; Hallen, J.; Clenin, G.; Villiger, B.; Marti, B. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
To compare the effects of two different volumes of altitude training during a five-month pre-season training period on erythropoiesis and performance in elite cross-country skiers, a control group (CG7; n=7) completed three oneweek altitude training periods (ATP I-III), while the altitude group (AG7; n=7) lengthened ATP I and ATP III by two live high-train low (LHTL) weeks each. Due to illness in three subjects, only four AG7 athletes completed ATP III; their results are reported as AG4. Blood parameters were measured several times and performance parameters were measured before and after the five-month training period. After ATP I, hemoglobin mass (Hbmass) and red cell volume (RCV) increased in AG7 by 4.3% (p<0.001) and 4.6% (p<0.001), respectively, while there was no change in these parameters in CG7. After ATP III, Hbmass increased further in AG4 (+6.8%; p<0.05) whereas no changes were seen in either AG7 or CG7. RCV decreased in CG7 (p<0.001), and remained unchanged in AG7 and AG4 after ATP III while mean corpuscular volume (MCV) decreased in all groups (AG7, p<0.001; CG7 and AG4, p<0.01). VO2max increased in AG7 (+6.4%; p<0.01) and was unchanged in CG7, while time to exhaustion (TTE) increased similarly in all groups. In conclusion, Hbmass increased by 4-5% after one three-week ATP and increased further with an additional three-week ATP several weeks later, despite decreased MCV and unchanged RCV. Seven altitude training weeks (3+1+3) during a five-month training period seem to increase aerobic performance more than three altitud training weeks (1+1+1).